ANALISIS PENGARUH BID-ASK SPREAD, TURNOVER, VOLATILITAS TERHADAP DISPOSITION EFFECT PADA PASAR MODAL INDONESIA (Studi Kasus pada Saham LQ45 Periode Januari 2010 – Juni 2015) - Sembiring, Vijai; Arfinto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
Disposition effect is the tendency of investor to sell their winning investment too soon and hold losing investment too long. Identifying the causes of disposition effect is important to determine whether the disposition effect make the market inefficient. This study aims to analyze the effect of bid-ask spread, turnover, volatility, market return, firm size, and book to market ratio of the disposition effect. The population in this study is a company listed in Indeks LQ45 the Indonesia Stock Exchange during January 2010 – June 2015. Total of samples to be taken is 44 companies. The analytical method used is multiple linier regression. The research model used in this study had escaped from four test, test normality assumption, namely classic multikolinearitas, autokorelasi, and heteroskedastisitas. All independent variable that exist in the test in the dependent variable to simultan. Independent variable in this research describes a number of 20,7% of the dependent variable explained by 79,3% while the other factors. The results of this study showed that the bid-ask spread, volatility, market return, firm size significantly effect on disposition effect. Whereas turnover and book to market have no significant effect on disposition effect.